2011
DOI: 10.1093/molbev/msr271
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of the Teneurins: Conserved Features and Premetazoan Ancestry

Abstract: Teneurins are type II transmembrane proteins expressed during pattern formation and neurogenesis with an intracellular domain that can be transported to the nucleus and an extracellular domain that can be shed into the extracellular milieu. In Drosophila melanogaster, Caenorhabditis elegans, and mouse the knockdown or knockout of teneurin expression can lead to abnormal patterning, defasciculation, and abnormal pathfinding of neurites, and the disruption of basement membranes. Here, we have identified and anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
150
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(155 citation statements)
references
References 43 publications
5
150
0
Order By: Relevance
“…Within the central brain, Ten-a mutation causes midline fusion defects within the central complex), a brain structure implicated in sensory integration and locomotion (26). Ten-a is highly conserved from insects to mammals (27). To validate the role of Ten-a in modulating variability in turning bias, we used a null allele (Ten-a cbd-KS96 ; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Within the central brain, Ten-a mutation causes midline fusion defects within the central complex), a brain structure implicated in sensory integration and locomotion (26). Ten-a is highly conserved from insects to mammals (27). To validate the role of Ten-a in modulating variability in turning bias, we used a null allele (Ten-a cbd-KS96 ; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we wanted to explore whether pre-bilaterians comprise homologues of single transmembrane helix post-synaptic proteins. Interestingly, a recent evolutionary analysis on teneurins, an endogenous ligand of latrophilins (see above), suggested that these single-pass transmembrane proteins, which are involved in neurogenesis, were absent in the genomes of sponges, cnidarians, placozoans and ctenophores (Tucker et al, 2012). This implies that the pre-bilaterian adhesion GPCRs that are similar to family I do not have ligands or interactions partners analogous to those in vertebrates.…”
Section: Single-pass Membrane Proteins -A Possible Interaction Partnementioning
confidence: 99%
“…In M. brevicollis, LGT from both eukaryotic and prokaryotic sources has been proposed to be responsible for the gain of stress-related genes [60]. Stramenopile-derived genes are thought to be unusually frequent in M. brevicollis [57], including genes linked with the evolution of multicellularity [61]. Diatoms are believed to have gained some of their biosilicification machinery (related to longchain polyamine formation) from LGT [62] in addition to other diatom-specific metabolic pathways [58].…”
Section: (D) Proposed Structure and Function Of Choanoflagellate Silimentioning
confidence: 99%